The broad spectrum 2-oxoglutarate oxygenase inhibitor N-oxalylglycine is present in rhubarb and spinach leaves. (September 2015) - Al-Qahtani, Khalid; Jabeen, Bushra; Sekirnik, Rok; Riaz, Naheed; Claridge, Timothy D.W.; Schofield, Christopher J.; McCullagh, James S.O.
Graphical abstract: The synthetic broad-spectrum 2-oxoglutarate oxygenase inhibitor N -oxalylglycine (NOG) is found to be present as a natural product in Rheum rhabarbarum (rhubarb) and Spinach oleracea (spinach) leaves but not Escherchia coli or human embryonic kidney cells (HEK 293T). Highlights: Synthetic N -oxalylglycine (NOG) identified as a natural product. Oxygenase inhibitor found in spinach and rhubarb leaves. N -oxalylglycine not found in broccoli, watercress, bacterial or mammalian cells. N -oxalyl- L -alanine (NAA) also found in spinach and rhubarb leaves. Abstract: 2-Oxoglutarate (2OG) and ferrous iron dependent oxygenases are involved in many biological processes in organisms ranging from humans (where some are therapeutic targets) to plants. These enzymes are of significant biomedicinal interest because of their roles in hypoxic signaling and epigenetic regulation. Synthetic N -oxalylglycine (NOG) has been identified as a broad-spectrum 2OG oxygenase inhibitor and is currently widely used in studies on the hypoxic response and chromatin modifications in animals. We report the identification of NOG as a natural product present in Rheum rhabarbarum (rhubarb) and Spinach oleracea (spinach) leaves; NOG was not observed in Escherchia coli or human embryonic kidney cells (HEK 293T). The finding presents the possibility that NOG plays a natural role in regulating gene expression by inhibiting 2OG dependent oxygenases. This has significance because tricarboxylic acid cycle (TCA) intermediate inhibition of 2OG dependent oxygenases has attracted major interest in cancer research.